2020
DOI: 10.1155/2020/5707106
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Mongolian Medicine RuXian‐I on Hyperplasia of Mammary Gland Induced by Estrogen/Progesterone through CRYAB‐Promoted Apoptosis

Abstract: The traditional Mongolian medicine (TMM) RuXian-I is an empirical formula specifically used for treating the hyperplasia of mammary gland (HMG) in clinic based on the principles of traditional Mongolian medicine, but the treatment mechanism is not completely clear. In this paper, we elaborated the mechanism of RuXian-I in the treatment of HMG induced by estrogen and progestogen from its toxicity and activity. Firstly, RuXian-I exhibited no toxic effect on HMG rats through no changes of body weight and food int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Furthermore, it has been reported that the disturbance of sex hormones, particularly estrogen and progesterone, is the primary cause and defining feature of MGH: estrogen stimulation can accelerate breast proliferation, whereas progesterone can facilitate the growth and maturation of breast acinous cells and resist the proliferation impact of estrogen (Kleinberg et al, 2011;Chang et al, 2014). In other words, high levels of E 2 or a lack of P cause estrogen to stimulate breast epithelium for an extended period without the protection of progesterone, resulting in significant mammary tissue hyperplasia (Liu et al, 2020). As a result, the above results confirmed that HHXYT could inhibit the symptoms of MGH visibly.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that the disturbance of sex hormones, particularly estrogen and progesterone, is the primary cause and defining feature of MGH: estrogen stimulation can accelerate breast proliferation, whereas progesterone can facilitate the growth and maturation of breast acinous cells and resist the proliferation impact of estrogen (Kleinberg et al, 2011;Chang et al, 2014). In other words, high levels of E 2 or a lack of P cause estrogen to stimulate breast epithelium for an extended period without the protection of progesterone, resulting in significant mammary tissue hyperplasia (Liu et al, 2020). As a result, the above results confirmed that HHXYT could inhibit the symptoms of MGH visibly.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Liu et al demonstrated that the traditional mongolian medicine RuXian-I also known as "Hu hun e ru le" has protective and therapeutic effects on HMG rats induced by estrogen and progestogen possibly via promoting apoptotic pathway regulated by CRYAB and is a promising agent for treating HMG. RuXian-I inhibit the upregulation level of antiapoptotic protein CRYAB of HMG rats and promote mammary gland cell apoptosis of HMG rats via increases of promoting apoptosis protein caspases-3, 8, and 9 and Bax and tumor suppressor protein p53, decreases of antiapoptosis protein Bcl-2, and release of cytochrome c [5][6][7]. A meta-analysis conducted by Li et al revealed that using Ru-Pi-Xiao, chinese traditional medicine, in combiantion with tamoxifen could exhibit better therapeutic effects against MGH than that of tamoxifen alone (OR: 3.79; 95% CI: 3.09-4.65; p < 0.000.…”
Section: Introductionmentioning
confidence: 98%
“…E 2 stimulates the mammary gland tissue and causes excessive proliferation of mammary epithelial cells, and P promotes the development and maturation of mammary gland follicles and counteracts the excessive proliferation of mammary tissue cells. 2 The simultaneous increase in E 2 content and reduction in P content in the body lead to long-term stimulation of the mammary gland tissue by E 2 and attenuates protection by P, 3 thereby causing excessive hyperplasia of mammary gland ducts and lobules and incomplete replication. 4 Studies have shown that mediating the activation of the Raf-1/MEK/ERK signaling pathway can block the cell cycle, 5 inhibit cell proliferation, 6 and induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%